2019
DOI: 10.1002/jnr.24525
|View full text |Cite
|
Sign up to set email alerts
|

The new insights into human brain imaging after stroke

Abstract: Over the last two decades, developments of human brain stroke imaging have raised several questions about the place of new MRI biomarkers in the acute management of stroke and the prediction of poststroke outcome. Recent studies have demonstrated the main role of perfusion‐weighted imaging in the identification of the best cerebral perfusion profile for a better response after reperfusion therapies in acute ischemic stroke. A major issue remains the early prediction of stroke outcome. While voxel‐based lesion‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 113 publications
0
15
0
Order By: Relevance
“…Non-invasive in vivo imaging techniques allow a longitudinal estimation of the brain damage location and extent and contribute to our understanding of the evolution of damage after stroke. Although the extent of damage is a critical determinant, the functions served by the brain areas damaged (e.g., language, motor, or cognition) and the nature of damage (e.g., necrosis, edema, axonal damage) determine the final disabilities [ 239 ].…”
Section: Evaluation Of Stroke Damage In Swine By Neuroimagingmentioning
confidence: 99%
“…Non-invasive in vivo imaging techniques allow a longitudinal estimation of the brain damage location and extent and contribute to our understanding of the evolution of damage after stroke. Although the extent of damage is a critical determinant, the functions served by the brain areas damaged (e.g., language, motor, or cognition) and the nature of damage (e.g., necrosis, edema, axonal damage) determine the final disabilities [ 239 ].…”
Section: Evaluation Of Stroke Damage In Swine By Neuroimagingmentioning
confidence: 99%
“…Finally, recent results also suggested that the greatest long-term risk of dementia might occur in patients with severe stroke (Dichgans, 2019). These indicate that stroke is not just an associate, but can be an initiator of cognitive deterioration (Sagnier and Sibon, 2019). Ischemia triggers a cascade of events in the brain, including impediment of aerobic energy metabolism, extensive generation of reactive oxygen spices, and mitochondrial injury among others (George and Steinberg, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Computed tomography, magnetic resonance diffusion weighted imaging (DWI) and perfusion weighted imaging (PWI) have been commonly used to diagnose acute stroke and to evaluate its therapeutic effect and clinical prognosis ( Scheldeman et al, 2020 ; Suh et al, 2019 ; Zhu et al, 2019 ). Among the neuroimaging techniques mentioned above, previous studies showed that DWI is the most valuable approach for the detection of acute stroke ( Heiss & Zaro-Weber, 2019 ; Sagnier & Sibon, 2019 ; Scheldeman et al, 2020 ; Simonsen et al, 2015 ; Wolman et al, 2018 ; Wouters et al, 2016 ). The ischemic lesions exhibit themselves via evident hyperintensity on DWI, and accompanied by a decrease in apparent diffusion coefficient (ADC) values ( Liu et al, 2019 ; Wolman et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%